Factors Affecting the Interest of Entrepreneurship Students of Universitas Negeri Padang to Maintain Their Business - Ribaina Novi; Syuraini Syuraini (Universitas Negeri Padang, 2020)
The purpose of this study was to determine the factors that influenced the entrepreneurial interest of Padang state university students to maintain their business, namely: 1) the influence of the family environment, 2) income expectations, 3) entrepreneurship education. This research is a descriptive study with a qualitative approach. The subjects of this study were the general chairman of UPKK and members of UPKK who already had their own businesses. Data collection is done by using the method of observation, interviews and documentation. Techniques used in data analysis are data display, data reduction and conclusion making. The results showed that the factors influencing student entrepreneurial interest: 1) Family environment, all informants were supported by their families for entrepreneurship even though not all of the informant's families came from entrepreneurial families. 2) Income expectations all informants said that the income expectation factor made them still maintain their business until now. 3) Entrepreneurship education, the existence of entrepreneurship education on campus makes all informants understand the world of entrepreneurship because learning entrepreneurship education makes informants understand what they will do later with their efforts.Keywords: Entrepreneurial Interest, Factors Affecting Interest